Effect of Instructions in the Language Laboratory on English Pronunciation of Pupil Teachers (Educational quest (New Delhi), 2013)
Good communication in English depends upon proper pronunciation. Proper pronunciation means reproducing the sound of the word through speech in such a way that any fluent speaker of the language would effortlessly know and understand the message. Improper pronunciation causes a breakdown in communication and requires more effort to understand. Poor pronunciation can cause a negative first impression. People who cannot pronounce English properly are often thought of as less literate or intelligent. Therefore teachers and learners of any language must not neglect the spoken aspect of language while teaching and learning various skills. They should neither underestimate nor neglect the importance of correct pronunciation in development of language skills. But in our schools, we teach English as a knowledge subject and not as a skill. As a result, even after learning English for so many years students are not able to speak it properly. They don't find themselves confident enough to use it in day to day life. Even our future English teachers are not good communicators in English language. In this study an attempt was made to study the effect of instructions in the language laboratory on English Pronunciation of Pupil teachers. The sample of the study was comprised of 33 pupil teachers of K.C. College of Education; Nawanshahr. Self prepared English Pronunciation Test was used in this study. The students of experimental group were given instructions in Language Laboratory. On the other hand, the students of the Control Group continued with their Routine Activities of the classroom. This continued for 30 working days. The results of the study indicated that Instructions in the Language Laboratory were found to be superior to routine activities of classroom in improving English Pronunciation of pupil teachers.